2012
DOI: 10.1186/1477-7819-10-189
|View full text |Cite
|
Sign up to set email alerts
|

Primary yolk sac tumor of seminal vesicle: a case report and literature review

Abstract: BackgroundYolk sac tumor (endodermal sinus tumor) is a rare malignant germ cell tumor arising in the testis or ovary. Extragonadal yolk sac tumor is even rarer and has only been described in case reports. Due to the rarity of the tumors, the appropriately optimal treatment remains unclear. We report a case of yolk sac tumor in the seminal vesicle.CaseA 38-year-old Asian male presented with gross hematuria and hemospermia. Transrectal ultrasound scan showed a solid mass in the left seminal vesicle and the scrot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…The histogenesis of extragonadal YST remains controversial. There are currently two theories that may explain the occurrence of primary GCT at extragonadal sites; the first is the aberrant differentiation of somatic cells, while the second is the malignant transformation of remnant of germ cells along the pathway of migration ( 6 , 7 ). The latter may be more feasible for explaining the location of the YST in the present case.…”
Section: Discussionmentioning
confidence: 99%
“…The histogenesis of extragonadal YST remains controversial. There are currently two theories that may explain the occurrence of primary GCT at extragonadal sites; the first is the aberrant differentiation of somatic cells, while the second is the malignant transformation of remnant of germ cells along the pathway of migration ( 6 , 7 ). The latter may be more feasible for explaining the location of the YST in the present case.…”
Section: Discussionmentioning
confidence: 99%
“…There has been one previously reported case of YST involving the seminal vesicles. [ 7 ] This was treated with BEP chemotherapy followed by excision of the seminal vesicles. Subsequent biochemical relapse was treated with further BEP chemotherapy and pelvic lymphadenectomy for nodal metastases.…”
Section: Discussionmentioning
confidence: 99%
“…The pineal gland and the sacrococcygeal area are less frequently encountered as anatomical locations for EGCT 2,3 . However, there have been described isolated cases in the bladder, prostate, seminal vesicle, vulva, placenta, uterus and kidney [4][5][6][7][8][9] . It has been observed that females are less affected than males, with a higher incidence in white males (56.3/1 million) 1 .…”
Section: Introductionmentioning
confidence: 99%